The effect of MAP on the growth and survival of Escherichia coli O157:H7 and Staphylococcus aureus in chilled minced beef - Buys, E.M. (Elna Maria) (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2012.